Pathway Pathology : Histological Differences Between ErbB/Ras and Wnt Pathway Transgenic Mammary Tumors - Rosner, Andrea (American Society for Investigative Pathology, 2002)
To study phenotype-genotype correlations, ErbB/Ras pathway tumors (transgenic for ErbB2, c-Neu, mutants of c-Neu, polyomavirus middle T antigene (PyV-mT), Ras, and bi-transgenic for ErbB2/Neu with ErbB3 and with progesterone receptor) from four different institutions were histopathologically compared with Wnt pathway tumors [transgenes Wnt1, Wnt10b, dominant-negative glycogen synthase kinase 3-β, β-Catenin, and spontaneous mutants of adenomatous polyposis coli gene (Apc)]. ErbB/Ras pathway tumors tend to form solid nodules consisting of poorly differentiated cells with abundant cytoplasm. ErbB/Ras pathway tumors also have scanty stroma and lack myoepithelial or squamous differentiation. In contrast, Wnt pathway tumors exhibit myoepithelial, acinar, or glandular differentiation, and, frequently, combinations of these. Squamous metaplasia is frequent and may include transdifferentiation to epidermal and pilar structures. Most Wnt pathway tumors form caricatures of elongated, branched ductules, and have well-developed stroma, inflammatory infiltrates, and pushing margins. Tumors transgenic for interacting genes such as protein kinase CK2α (casein kinase IIα), and the fibroblast growth factors (Fgf) Int2/Fgf3 or keratinocyte growth factor (Kgf/Fgf7) also have the Wnt pathway phenotype. Because the tumors from the ErbB/Ras and the Wnt pathway are so distinct and can be readily identified using routine hematoxylin and eosin sections, we suggest that pathway pathology is applicable in both basic and clinical cancer research.